New Brachiopod records and considerations on the Tivertonia-streptorhynchus (Moscovian) and Costatulumus amosi (Sakmarian–artinskian) faunas from western Argentina: the key sections at Quebrada Agua del Jagüel and Quebrada Santa Elena revisited - Taboada, Arturo Cesar (2014)
The brachiopod Coolkilella aredesi sp. nov. and Calytrixia piersoni sp. nov. are proposed on the basis of specimens from the Del Salto, Río del Peñón and Agua del Jagüel formations. Their biostratigraphic implications are discussed together with new records of Septosyringothyris (Precosyringothyris) jaguelensis Lech and Streptorhynchus inaequiornatus Leanza at the top of the latter unit. The stratigraphic record, paleontological content and age of both the Tivertonia-Streptorhynchus assemblage (Moscovian) and the younger Costatumulus amosi fauna (Sakmarian–Artinskian) were reviewed and assessed based on outcrops at Quebrada Agua del Jagüel and Quebrada Santa Elena. Faunal content confirms the most recent stratigraphic, biostratigraphic and paleoclimatic frameworks. These a diachronic nature of the Agua del Jagüel and Cordón del Jagüel formations, supporting the absence of an early Permian glacial event in western Argentina.